Density and Magnetic Properties of Barium Ferrite from BaFe12O19 Nanoparticles Prepared by Microemulsion Method - Kuncoro, Handoko Setyo; Sulistarihani, Naniek; Manullang, Ria Julyana; Astari, Ratih Resti (Balai Besar Keramik, 2015)
The density and magnetic properties of barium ferrite from BaFe12O19 Nanoparticles prepared by microemulsion method have been studied by comparing with the properties of micro-scaled BaFe12O19 prepared by metallurgical method. The preceding preparation consists of emulsification process, mixing, aging, centrifuging/separation, drying, grinding, and calcination at temperature of 900 oC, which brings on Â the BaFe12O19 nanoparticles powder as its final product. Then, the obtained powders have been formed at compaction pressure of 200 Kg/cm2 and sintered at temperature of 1100 oC. The indications of formed BaFe12O19 nanoparticles have been confirmed via XRD and TEM testings which their dimension sizes are under 100 nm. Based on density measurements, the density of barium ferrite prepared by microemulsion method is higher than that of by metalurgical method (i.e. 5,3 gr/ml). While, the permagraph examinations have indicated that both remanence magnetic induction (2.49 kOe) and maximum energy product values (0.47 MGOe) of barium ferrite prepared by microemulsion method are higher about 1.22 and 1.47 times, respectively.